Preparation of Basundi Using Ashwagandha for value addition - Modi, Lalita; Pinto, Suneeta; Prajapati, P. S.; Suvera, Priyanka (Indian Journal of Dairy Science, 2023)
The objectives of the present study was to develop an acceptable quality basundiincorporated with Ashwagandha powder . Four batches of Basundi were prepared usingthree different levels of Ashwagandha powder viz. 0 (P1), 0.20 (P2), 0.25 (P3) and 0.30 (P4)% (w/w of milk). Addition of ashwagandha powder up to 0.25% i.e. P3 was found to beacceptable. In order to evaluate the effect of level of sucrose on its acceptability, P3 Basundiwas incorporated with three level of sugar viz. 5, 6 and 7 % (w/w of milk) and it was foundthat Basundi prepared using 6 % sugar was most acceptable. Cardamom was found mostsuitable background flavour on basis of sensory score among three different flavors viz.cardamom, saffron and nutmeg when added at the rate of 0.25 % w/w of Basundi. Based onthe results obtained in this study a method for preparing Basundi using Ashwagandha powderwas developed. The standardized method involved use of mixed milk (fat: SNF ratio of 0.5),addition of 0.25 % Ashwagandha powder and 6 % sugar (w/w of milk) and using cardamomflavour @ 0.25% w/w of Basundi. The total score of the developed product was 90.13indicating that the product could be graded as excellent quality based on the 100 point scorecard suggest by BIS for sensory evaluation of milk.